Upaya Peningkatan Pengetahuan Dengan Pendidikan Kesehatan Pada Anak Dengan DBD Di RSPA Boyolali - Suhariyono, Eko Agus, Irdawati, S.Kep.,Ns., M.Si. Med (2016)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection, and is transmitted through the bite of female mosquitoes Aedes Aegypti and Aedes Albopictus that have been infected by dengue virus, dengue hemorrhagic fever (DHF) are found in tropical and sub-tropical , This disease often leads to Extraordinary Events in several districts / cities in Indonesia. In 2012, dengue cases were reported in Indonesia 90.245 people with the death of 816 people. In 2013, Incident Rate (IR) DHF is 45.85 / 100,000 population. Dengue hemorrhagic fever is a contagious disease that is based on environment, therefore the incidence of DHF can be repeated, it must be prevented in order to avoid extraordinary events, by providing health education as one of Nursing lack of knowledge. Provide nursing care in children with DHF by way of increasing knowledge on the family not to become extraordinary events. Case study method to solve the problem by providing nursing care to Increase Knowledge of the Health Education in Children with DHF In RSPA Boyolali, the first step is the assessment, data analysis, intervention, implementation and evaluation of nursing. After the act of nursing health education for 20 Minutes on patients and families understand about understanding, modes of transmission, signs and symptoms of dengue fever, a mosquito breeding sites, mosquito characteristics, home management and the prevention of dengue disease in the environment. The most effective way to prevent this disease is a method 3M plus, namely closing, drain, buried, with providing information about dengue in the family, so that the incidence of DHF can then be prevented and not be extraordinary events, because knowledge of the family has increased.